Rocky Eyewear / Imran Danial Ahmad Latif - Ahmad Latif, Imran Danial (2021)
Online marketing is a strategy of utilizing web-based platforms to disseminate a message regarding a firm’s brand, products, or services to its potential customers. Some of popular options for companies to promote their offerings are through email, social media, display advertising, and search engine optimization. This report provides an insight into how Rocky Eyewear utilizes strategies and techniques on its social media channel to attract customers into buying its products. Rocky Eyewear is a brand that sells eyewear products for customers who are looking for optical solutions as well as customers who are looking to style up their appearances. It is understood that Rocky Eyewear is a well-known eyewear brand that has been the choice for many customers in South East Asia with the highest market share being in Malaysia. The purpose of this research is to understand how the brand got to where it is today through online marketing. Clever methods for the local brand promoting its products are through teasers as well as soft-sell and hard sell marketing techniques. Upon the launch of the brand, teasers and soft-sell helps the brand to build up anticipation among customers where it creates curiosity among them as to what Rocky Eyewear is all about. The hard-sell technique is the part where the brand reveals what it sells and presents the speciality of its products compared to its rivals who are in the same business. The content of this report includes the samples of each strategy that Rocky Eyewear implements.